Proses Audit Atas Aset Biologis: Studi Kasus di PT Andini Agro Loka oleh KAP Kanaka Puradiredja Suhartono - Achmad Ridwan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The audit of Biological Assets is a systematic examination to assess whether the biological assets reported by the company have been presented reasonably free from material misstatement in accordance with Indonesian Financial Accounting Standards (SAK). This apprenticeship report describes and discusses the process of conducting an audit of Biological Assets at PT AAL. The audit process starts with planning the audit, conducting the audit and reporting the audit. PT AAL is a company in the field of breeding and cattle fattening. The audit process was carried under the guidance of the Public Accounting Firm (KAP) Kanaka Puradiredja, Suhartono in accordance with the audit guidelines compiled by the KAP. Based on the audit process, that PT AAL has presented biological assets fairly in accordance with PSAK 69.